2009
DOI: 10.1097/jto.0b013e3181b27799
|View full text |Cite
|
Sign up to set email alerts
|

The IASLC Lung Cancer Staging Project: Proposals Regarding the Relevance of TNM in the Pathologic Staging of Small Cell Lung Cancer in the Forthcoming (Seventh) Edition of the TNM Classification for Lung Cancer

Abstract: This analysis further strengthens our previous recommendation to use TNM staging for all SCLC cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
298
2
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(320 citation statements)
references
References 39 publications
13
298
2
7
Order By: Relevance
“…To our knowledge, only a few articles reported that age was the independent prognostic factors for pulmonary NET (Filosso et al, 2014), which was likely attributable to the good immunity and resistance to the illness of young patients. TNM staging was also effective in predicting the outcome of pulmonary NET, similar to what Vallieres E reported (Vallieres et al, 2009) However, it was strange that nodal status did not predict the prognosis. A previous report showed that lymph node sampling might be inaccurate in evaluating the nodal status (Massard et al, 2006).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…To our knowledge, only a few articles reported that age was the independent prognostic factors for pulmonary NET (Filosso et al, 2014), which was likely attributable to the good immunity and resistance to the illness of young patients. TNM staging was also effective in predicting the outcome of pulmonary NET, similar to what Vallieres E reported (Vallieres et al, 2009) However, it was strange that nodal status did not predict the prognosis. A previous report showed that lymph node sampling might be inaccurate in evaluating the nodal status (Massard et al, 2006).…”
Section: Discussionsupporting
confidence: 62%
“…In this study, in order to compare the clinical, pathological and prognostic differences between different types of pulmonary NET, we used the 7th edition of American Joint Committee On Cancer/Union For International Cancer Control (AJCC/UICC) TNM staging system (Edge et al, 2010). The reason for applying the TNM staging system was chiefly on the basis of two large-scale surveys on carcinoid tumors and SCLC from International Associational Association for the Study of Lung Cancer (IASLC) database (Travis et al, 2008;Vallieres et al, 2009). OS was the main endpoint of this study.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%
“…Lung cancer was ultimately diagnosed in 11 of the participants, including two cases with pulmonary hilus enlargements. According to the latest Seventh Edition of the TNM Classification for Lung Cancer [16], 10 patients (90.91 %) were in stage I, comparing with one (9.09 %) in a status of liver metastasis. Figure 1 showed a patient with a 15-mm noncalcified nodule in the baseline DR scan, and the following surgery confirmed a diagnosis of adenocarcinoma.…”
Section: The Scoring Questionnaire and Demographics Characteristics Omentioning
confidence: 99%
“…Mediastinal LN dissection was routinely performed; in some patients, for example T1 tumor in patients age >70 years, A LN sampling was done. LN stations were defined according to the IASLC classification (18). The N2 level included ipsilateral station 2-station 9, N1 level included ipsilateral station 10-station 14, N3 level included station 1, contralateral mediastinal LN, and hilar nodes.…”
Section: Patient Selectionmentioning
confidence: 99%